Engineering of Tire Pressure Controlling Device: An Invention Towards Successful Product Development - Sivarao, Subramonian; T., Joseph Sahaya Anand; Mohd Warikh, Abd Rashid (IJENS, 2009)
Tire pressure plays an important role in ensuring safe and economical driving. Even then, many vehicles with under inflated tires are observed to be on the road due to the unawareness of the fact that properly inflated tires can safe tire life up to 20% which is nine months more of its life span. It can also save fuel from 4% to 10%, increase braking efficiency up to 20%, lightens steering system and ease self steer. Improper maintenance and operation failure of air pressure kiosks are the main reason why users seldom inflate their tires at the gas stations. Besides that, long awaiting queue at the kiosk and not knowing the exactly required tire pressure of their own vehicle is another cause for tires running with improper pressure. Therefore, a method of how to ease the users to inflate their tires is engineered and invented. Automatic Tire Pressure Controller (ATPC) has been idealized to ensure correct pressure is inflated into the tires regardless of the setting on the pressure source: e.g. kiosk, compressor, foot inflator, etc. The device will alert the user upon reaching the appropriate pressure by a hissing sound. This product attracts many users especially ladies who often being the second driver who are always unsure of the pressure of their tires.